2017
DOI: 10.1111/tme.12495
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a targeted blood management programme on allogeneic blood transfusion in abdominal aortic aneurysm surgery

Abstract: Such low levels of allogeneic transfusion have not been reported previously. We hypothesise that this is due to the additional blood management contributions of the specialised cell salvage practitioners and collaboration with the rest of the vascular surgical team. These results support the development of pre-operative anaemia clinics. Overall the service runs at a profit to the trust.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…22,23 Our results also reinforce the unexpected maintenance of coagulation in patients with massive blood loss, which we reported in our previous paper. 6 This contradicts current guidelines for the management of patients experiencing massive blood loss. None of our patients developed significant coagulopathy or hyperfibrinolysis as measured by TEG.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…22,23 Our results also reinforce the unexpected maintenance of coagulation in patients with massive blood loss, which we reported in our previous paper. 6 This contradicts current guidelines for the management of patients experiencing massive blood loss. None of our patients developed significant coagulopathy or hyperfibrinolysis as measured by TEG.…”
Section: Discussionmentioning
confidence: 97%
“…Intraoperative cell salvage (ICS) has been an established technique for >40 years to minimise blood loss and reduce allogeneic blood transfusion as part of PBM in patients undergoing major surgery 3–5 . We previously described the effective use of specialised ICS techniques as part of our PBM strategy to reduce allogeneic transfusion in 171 consecutive patients undergoing AAA surgery including the use of specialist PBM practitioners 6 . Out of those 171 patients, seven lost >70% of their estimated blood volume but none of those seven developed thromboelastographic (TEG) coagulation changes sufficient to require intraoperative intervention with any allogeneic blood components.…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective study evaluating aneurysm surgery, VET parameters never reached a preset threshold for intervention. 60 In a smaller study in cardiac surgery, patients with large-volume autologous blood transfusions had a paradoxical procoagulant effect when evaluated by VET. 61 More research is needed in this area to explore the use of VET in liver transplants where blood salvage is used, as cirrhotic patients have markedly different coagulation profiles compared with patients with vascular disease.…”
Section: Cell Salvage Utilization During Noncoagulopathic Bleedingmentioning
confidence: 99%
“…Shander et al43 demonstrated that the total cost per unit of fresh frozen plasma transfused was $409 and $1608 per patient transfused. Although such costly elements, inappropriate and avoidable transfusion contributes significantly to health care budgets 40,44,45. Implementation of PBM initiatives to guide bleeding/coagulation management and to manage anemia has resulted in significant cost saving and improved patient outcomes 23,46-49…”
Section: Transfusion Is Not a Benign Therapymentioning
confidence: 99%